Stimulation of exosome release by extracellular DNA is conserved across multiple cell types. (12th July 2018) - Iliev, Dimitar; Strandskog, Guro; Nepal, Arpita; Aspar, Augusta; Olsen, Randi; Jørgensen, Jorunn; Wolfson, Deanna; Ahluwalia, Balpreet Singh; Handzhiyski, Jordan; Mironova, Roumyana
Abstract : Exosomes are distinguished from other types of extracellular vesicles by their small and relatively uniform size (30–100 nm) and their composition which reflects their endo‐lysosomal origin. Involvement of these extracellular organelles in intercellular communication and their implication in pathological conditions has fuelled intensive research on mammalian exosomes; however, currently, very little is known about exosomes in lower vertebrates. Here we show that, in primary cultures of head kidney leukocytes from Atlantic salmon ( Salmo salar ), phosphorothioate CpG oligodeoxynucleotides induce secretion of vesicles with characteristics very similar to these of mammalian exosomes. Further experiments revealed that the oligonucleotide‐induced exosome secretion did not depend on the CpG motifs but it relied on the phosphorothioate modification of the internucleotide linkage. Exosome secretion was also induced by genomic bacterial and eukaryotic DNA in toll‐like receptor 9‐negative piscine and human cell lines demonstrating that this is a phylogenetically conserved phenomenon which does not depend on activation of immune signaling pathways. In addition to exosomes, stimulation with phosphorothioate oligonucleotides and genomic DNA induced secretion of LC3B‐II, an autophagosome marker, which was associated with vesicles of diverse size and morphology, possibly derived from autophagosome‐related intracellular compartments. Overall, this work reveals a previously unrecognized biological activity of phosphorothioate ODNs and genomic DNA – their capacity to induce secretion of exosomes and other types of extracellular vesicles. This finding might help shed light on the side effects of therapeutic phosphorothioate oligodeoxynucleotides and the biological activity of extracellular genomic DNA which is often upregulated in pathological conditions. Abstract : In vitro, genomic DNA and phosphorothioate oligonucleotides stimulate release of extracellular vesicles (EVs) by diverse cell types. Secretion of EVs containing exosome markers and LC3B‐II – an autophagosome marker is upregulated in cultures of piscine and human cells. The presented data indicate that extracellular DNA has potential to induce secretion of different types of EVs through phylogenetically conserved mechanisms.